Prosaposin is a biomarker of mesenchymal glioblastoma and regulates mesenchymal transition through the TGF‐β1/Smad signaling pathway. Issue 1 (21st May 2019) - Jiang, Yang; Zhou, Jinpeng; Hou, Dianqi; Luo, Peng; Gao, Huiling; Ma, Yanju; Chen, Yin‐Sheng; Li, Long; Zou, Dan; Zhang, Haiying; Zhang, Ye; Jing, Zhitao
Abstract: Mesenchymal glioblastoma (GBM) is the most aggressive subtype of GBM. Our previous study found that neurotrophic factor prosaposin (PSAP) is highly expressed and secreted in glioma and can promote the growth of glioma. The role of PSAP in mesenchymal GBM is still unclear. In this study, bioinformatic analysis, western blotting and RT‐qPCR were used to detect the expression of PSAP in different GBM subtypes. Human glioma cell lines and patient‐derived glioma stem cells were studied in vitro and in vivo, revealing that mesenchymal GBM expressed and secreted the highest level of PSAP among four subtypes of GBM, and PSAP could promote GBM invasion and epithelial–mesenchymal transition (EMT)‐like processes in vivo and in vitro . Bioinformatic analysis and western blotting showed that PSAP mainly played a regulatory role in GBM invasion and EMT‐like processes via the TGF‐β1/Smad signaling pathway. In conclusion, the overexpression and secretion of PSAP may be an important factor causing the high invasiveness of mesenchymal GBM. PSAP is therefore a potential target for the treatment of mesenchymal GBM. © 2019 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd